2006
DOI: 10.1161/01.atv.0000201969.93348.74
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane A2/Prostaglandin H2 Receptor Activation Mediates Angiotensin II–Induced Postischemic Neovascularization

Abstract: Objective-We analyzed the involvement of thromboxane (TX) A 2 /prostaglandin (PG) H 2 (TP) receptor in ischemiainduced neovascularization in mice. Methods and Results-Unilateral hindlimb ischemia was induced by right femoral artery ligature in male C57BL/6J mice (nϭ7 per group). Animals were then treated with or without TP receptor antagonist (S18886, 5 or 10 mg/kg per day; ramatroban, 10 mg/kg per day) or aspirin (30 mg/kg per day) in drinking water for 21 days. Hindlimb ischemia raised plasma level of TXB 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
0
9
0
2
Order By: Relevance
“…Animal studies have shown that terutroban has beneficial effects on platelet aggregation, thrombus formation, vascular reactivity, and vessel wall proliferation [21,22,23]. In rabbits, it reduces the size of atherosclerotic plaque, intima-media thickness, intracellular adhesion molecule expression in endothelial cells, and monocyte/macrophage infiltration in the vessel walls [24].…”
Section: Rationalementioning
confidence: 99%
“…Animal studies have shown that terutroban has beneficial effects on platelet aggregation, thrombus formation, vascular reactivity, and vessel wall proliferation [21,22,23]. In rabbits, it reduces the size of atherosclerotic plaque, intima-media thickness, intracellular adhesion molecule expression in endothelial cells, and monocyte/macrophage infiltration in the vessel walls [24].…”
Section: Rationalementioning
confidence: 99%
“…Otherwise, low concentrations of TP agonists induce the angiogenesis in vitro , while high doses of TP agonists produce a biphasic response (Nie et al, 2000; Benndorf et al, 2008). There also is evidence suggesting that TBXA2 has opposite effects on angiogenesis depending upon the thromboxane receptor isoforms, a and b, in human endothelial cells (Ashton and Ware, 2004; Michel et al, 2006). At present, properties of zebrafish TP receptor are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…2(b)). 혈관내피세포막에 존재하는 TXA 2 수용체의 isoform의 종류는 α isoform과 β isoform이 존재한다고 알려져 있다 [15,16]. 트롬복산 수용체 작용제가 혈관내피세포를 자극하여 IL-8 발현 및 ERK1/2와 p38 신호전달 경로를 활성화 시킬 때 어떠한 종류의 막 수용 체의 isoform이 작용하는 지에 대한 연구는 추가적인 실험을 통해 규명해 낼 필요가 있을 것으로 생각된다.…”
Section: Ex Vivo 단핵구 부착법 (Ex Vivo Monocyte Adhesion Assay)unclassified
“…이러한 혈관 내피세포에서의 TXA 2 의 기능은 혈관내피세포막에 존재하 는 트롬복산 수용체 (thromboxane receptor, TP)를 통해 작용 한다. 트롬복산 수용체는 인간에서는 TPα과 TPβ, 두 가지 isoform을 가지고 있으며 이들의 활성이 죽상동맥경화증과 같은 혈관성 염증질환에 관여한다 [15,16]. 그리고 트롬복산 수용체의 발현 및 트롬복산 수용체의 리간드의 혈장 농도가 여러 가지 심혈관계 질환에서 증가되어 있다고 보고되고 있 다 [17,18].…”
unclassified